The Influence of the Piezoelectric Non-conservative Effect on the Bi-stable Vibration Energy Harvester - Tian, Yanping; Lu, Xinpei; Wang, Bin; Tang, Bo; Xu, Ming (Journal of Vibration Engineering & Technologies, 2024)
Background The power of low power devices, such as MEMS, soft electronics, sensors, are externally supplied by the chemical batteries. Comparing with the chemical batteries, the self-sufficient and maintenance-free energy supplying is a better alternative way. The vibration energy harvester (VEH) provides a self-sufficient solution for the low-power device, which savages various mechanical energy from the environment. Among the energy conversion principle, the piezoelectricity has received extensive attentions. Purpose Due to the complex internal dissipation mechanism (i.e., piezoelectric long-memory effect), the phenomenological relation of the mechanical input/output and the electrical output/input obeys a complicated law, which can be modeled as a Caputo fractional derivative differential relation. To reveal the influence of such fractional derivative circuit on the energy harvester is an important subject. Methods In this manuscript, we aim to evaluate the dynamic characteristics of the bi-stable energy harvester incorporating the piezoelectric nonconservative effect. Firstly, establish the governing equations composed of a second-order ordinary differential equation and a fractional derivative differential equation. Then, decouple the governing equations by using the harmonic balanced method, and obtain the voltage as an approximate function of the displacement and the velocity of the mechanical system. Finally, by adopting the equivalent nonlinearization method, the steady-state probabilistic density function of the system states, the mean-square voltage and the mean output power can be derived. Conclusion The results show that the mean-square voltage increases with the increase of the fractional order, which means the piezoelectric nonconservative behavior has a significant negative effect on the performance of the VEH. The non-conservative effects of the piezoelectric materials may be intensified for long-term working environment, our work can give an insight into such situations. Some crucial parameters such as electromechanical coupling coefficient and time constant ratio are discussed.